Probiotic potential of Lactococcus lactis GU967439 isolated from raw milk: an in vitro study (INNOTEC, 2024)
Native probiotic strains are chosen for the production of functional dairy products due to their technological advantages. The preliminary selection of these strains is based on different in vitro tests that predict their safety and functional properties. This study aimed to evaluate in vitro antibiotic resistance, the effect of the passage through the gastrointestinal tract, and the antimicrobial activity of the native strain Lactococcus lactis GU967439 isolated from raw milk from a farm in Nueva Helvecia, Colonia, Uruguay. Lactococcus lactis ATCC N° 11454, was used as reference. L. lactis GU967439 was susceptible to antibiotics against Gram positives. In addition, it was resistant to the simulation of gastric juice at pH 3, pancreatin and bile. The cell-free supernatant of L. lactis GU967439 presented in vitro activity against Staphylococcus aureus ATCC 6538, Staphylococcus aureus ATCC 29213, Enterococcus faecalis ATCC 29212, Listeria innocua ATCC 33090, Streptococcus bovis 2.5 (WT) and had better activity than L. lactis ATCC N° 11454.However, none of them inhibited Gram-negative indicators (Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 9027). These results allow for future studies to continue characterizing the probiotic potential of L.lactis GU967439.
Keywords: lactic acid bacteria; gastric resistance; antimicrobial activity; bacteriocins; antibiotic resistance